Устойчивость подкрепленных цилиндрических оболочек при комбинированном нагружении. - Гавриленко, Г.Д.; Мацнер, В.И. (Прикладная механика, 2010)
The method of calculation of critical loads of stiffened cylindrical shells is
suggested. The shells are subjected of combined loading (external pressure and longitudinal
axial loads). An effect of influence on critical loads quantity of ribs is studied analytically. Запропоновано новий підхід до проблеми стійкості ребристих циліндричних оболонок при дії поздовжніх сили і тиску. Наведено результати розрахунків для оболонок, підсилених
ребрами в двох напрямках.